Do the Portfolios of Small Investors Reflect Positive Feedback Trading? - Bange, Mary M. (Journal of Financial and Quantitative Analysis, 2000)
This study examines the stock market forecasts and portfolio allocation decisions of small individual investors, based on survey data for 1987-1994. When investors are bullish, they increase their equity holdings; when investors are bearish, they decrease equity holdings. The surveyed investors are unable to time the stock market successfully. However, the shifts in their portfolios reflect past market movements and are consistent with positive feedback trading. I. Introduction There can be no doubt that, over short horizons, stock price changes are highly unpredictable. Nevertheless, many individuals discover seeming in past prices and trade based on the expectation that the trends will persist. De Long, Shleifer, Summers, and Waldmann (1990) call these investors positive feedback traders.